Gait and trunk kinematics during prolonged turning in Parkinson's disease with freezing of gait. (July 2019) - Mitchell, Trina; Conradsson, David; Paquette, Caroline
Abstract: Introduction: Although turning during walking is known to trigger freezing of gait (FOG) in Parkinson's disease (PD), little is known about kinematic strategies used by individuals with PD and FOG while performing prolonged turning. Objective: Our aim was to compare gait and trunk kinematics during straight walking and continuous turning over 20-min in PD with and without FOG. Methods: 18 individuals with idiopathic PD (n = 9 with FOG, n = 9 without FOG), performed two 20-min walking tasks: straight ahead, and turning, in a laboratory setting in their OFF medication state. Accelerometer-based spatial and temporal gait parameters and trunk kinematics (range of motion, peak velocity, variability of range of motion and peak velocity) were analyzed. Results: During turning, PD with FOG reduced cadence more compared to PD without FOG ( P < 0.045 ), despite similar decline in stride velocity (28–32%) and stride length (24–27%). Participants with FOG had decreased variability of gait speed ( P < 0.011 ), stride length ( P < 0.035 ), frontal trunk range of motion ( P < 0.040 ) and peak trunk velocity ( P < 0.017 ) compared to PD without FOG during turning, whereas there was no difference between groups during straight walking. Gait speed variability and cadence between these two tasks differentiated the PD groups (sensitivity 89% and specificity 78%). Conclusions: We demonstrate that PD with FOG decreased cadence and reduced variability of walking speed, stride length, and lateral flexion of the trunk compared to PD without FOG during prolonged turning. These real-life gait markers are observable during lab-based gait that is similar to daily-life. Highlights: Prolonged turning reveals impaired gait and trunk kinematics in Parkinson's disease with freezing of gait. Individuals with freezing of gait have an impaired ability to adjust cadence. Those with freezing of gait also have reduced variability of stride length, gait speed, and frontal trunk motion. These gait and trunk deficits are able to differentiate between these two parkinsonian groups.